2019
DOI: 10.1002/iub.2104
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin inhibits hallmarks of cancer by targeting the PI3K/NF‐κΒ/STAT3 signalling axis in oral squamous cell carcinoma models

Abstract: Aberrant activation of the PI3K/Akt signalling pathway, a major driving force of diverse cellular processes has been implicated in tumour development and progression. Here, we report that astaxanthin (AXT), a potent antioxidant ketocarotenoid prevents cancer hallmarks by inhibiting PI3K/Akt and the associated downstream NF‐κB and STAT‐3 signalling pathways in SCC131 and SCC4 oral cancer cells as well as in the hamster buccal pouch carcinogenesis model. Using small molecule inhibitors of NF‐κB, STAT‐3 and PI3K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…This may be consistent with the known functions of microRNAs as regulators of several key tumor-related functions, including angiogenesis [23,24]. Interestingly, these data may provide evidence that miR-21 might be down-regulated among oral cancer stem cell sub-populations, a key regulator of PI3K/ Akt pathway [25,26]. These observations may be consistent with other studies that suggest control and regulation of the PI3K/STAT3/NF-kB signaling pathway may be more important to tumor functions than critical stem cell or cancer stem cell functions [27,28].…”
Section: Discussionsupporting
confidence: 78%
“…This may be consistent with the known functions of microRNAs as regulators of several key tumor-related functions, including angiogenesis [23,24]. Interestingly, these data may provide evidence that miR-21 might be down-regulated among oral cancer stem cell sub-populations, a key regulator of PI3K/ Akt pathway [25,26]. These observations may be consistent with other studies that suggest control and regulation of the PI3K/STAT3/NF-kB signaling pathway may be more important to tumor functions than critical stem cell or cancer stem cell functions [27,28].…”
Section: Discussionsupporting
confidence: 78%
“…PI3K is an essential mediator of H. pylori -induced AGS cell migration [ 59 ]. In previous studies, ASTX treatment reduced invasive behavior of breast cancer cells and oral carcinoma cells by inhibiting PI3K signaling [ 42 , 43 ]. In a recent study carried out with oral squamous cell carcinoma models, Kowshik et al reported that ASTX inhibits hallmarks of cancer by targeting the PI3K/NF-κΒ/STAT3 signaling axis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, ASTX treatment reduced invasive behavior of breast cancer cells and oral carcinoma cells by inhibiting PI3K signaling [ 42 , 43 ]. In a recent study carried out with oral squamous cell carcinoma models, Kowshik et al reported that ASTX inhibits hallmarks of cancer by targeting the PI3K/NF-κΒ/STAT3 signaling axis [ 43 ]. PLCγ is also an important mediator of cell migration in response to growth factor receptor activation [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Powerful antioxidant astaxanthin (AXT) causes inhibition of PI3K / Akt and downregulation of NF-ÿB and STAT-3 signaling pathways in an oral neoplastic cell which is demonstrated in the cell line of hamster buccal carcinogenesis model (Kowshik, 2019).…”
Section: Mechanism Of Targeted Therapy Drugs On Oral Cancermentioning
confidence: 99%